دراسة تأث رٌ المب دٌ الحشري Thiamethoxam على بعض الجوانب الفسلج ةٌ للجهاز التناسل لذكور الفئران musculus Mus - نجاح صبراسيل (University of Thi-Qar Journal of Science, 2019)
This study refers to role of treatment with doses (0.004,0.08 Mg/ Kg ,B.W.) of incecticide Thiamethoxam for (35) days in induction to make pathological changes in testes tissue of treated mice males and abnormality sperm as well as decreased in sperm concentration and viability sperm percentage ,that was significant (P<0.01) in the second group that treated with high dose إن المعاممة بالمبيد الحشرري Thiamethoxam بجرعتيررو ) 0.008,0.004 ممغم/كغرم مرن وزن الجسرم ( ولمردة (35) يوم أحدثت عدة تغي ا رت مرضية في نسيج الخصى لذكور الفئ ا رن المعاممة وتشوىات في أشكال النطف إضافة إلرى الأنخفراض في تركيز النطف و النسربة المئويرة لحيويرة النطرف إذ كران الترأثير معنويراً (p<0.01) فري حيوانرات المجموعرة الثانيرة المعاممرة بالجرعة العالية